2021
DOI: 10.5737/23688076314393398
|View full text |Cite
|
Sign up to set email alerts
|

The post-treatment return-to-work transition experience for breast cancer survivors under 50 years of age

Abstract: The purpose of this study is to explore the experience of cancer survivors less than 50 years of age, as they transition back to work after the end of treatment. Eight survivors took part in this exploratory qualitative study. The results of the iterative content analysis suggest that these survivors want to put their illness-focused life behind them and resume a “normal” existence, of which a return to work is an integral part. The return-to-work transition is also influenced by various personal, family and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The patients expressed their fears of their cancer recurring, and, in some cases, of death, now that their treatment process had concluded. Consistent with our research, another study found that women voiced concerns about the possibility of a recurrence of cancer (Fadhlaoui et al, 2021). Elmir et al also noted that women with breast cancer experienced panic and insecurity due to the fear of cancer recurrence after treatment (Elmir et al, 2010).…”
Section: (B) Transition From Active Treatment To Treatment-free Livingsupporting
confidence: 90%
“…The patients expressed their fears of their cancer recurring, and, in some cases, of death, now that their treatment process had concluded. Consistent with our research, another study found that women voiced concerns about the possibility of a recurrence of cancer (Fadhlaoui et al, 2021). Elmir et al also noted that women with breast cancer experienced panic and insecurity due to the fear of cancer recurrence after treatment (Elmir et al, 2010).…”
Section: (B) Transition From Active Treatment To Treatment-free Livingsupporting
confidence: 90%
“…Finally, the average rate of POBs ability to return to work after the treatment was well assessed. Return to work generally symbolizes the recovery (27) or a “return to the normality” (28). Since return to work is likely to be an outcome, seen as the therapy effect, it can also correspond to the end of the treatment when return to work seems successful (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…Socially, work is presented as a source of QoL that helps to re-establish identity and social relations for women with cancer [12]. Similarly, work provides a sense of normality and a future, allowing patients to feel again part of a society to which they contribute significantly [13].…”
Section: Introductionmentioning
confidence: 99%